2016
DOI: 10.1016/j.jpowsour.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

First-principles thermal modeling of hybrid pseudocapacitors under galvanostatic cycling

Abstract: This study presents a theoretical framework developed from first principles for predicting the spatiotemporal thermal behavior of hybrid pseudocapacitors under galvanostatic cycling. It accounts for irreversible and reversible heat generation in the electrolyte and in the electrodes due to Joule heating, electric double layer (EDL) formation, and redox reactions. Detailed numerical simulations were performed to investigate the different local heat generation rates and the temperature as functions of time and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…Pilon et al proposed a one‐dimensional continuum model to simulate the time‐dependent charging behavior of a hybrid capacitor consisting of a pseudocapacitive metal oxide electrode for lithium‐ion intercalation and a carbon electrode for EDL formation ( Figure a) . Ion diffusion, lithium‐ion intercalation, and redox reaction were simultaneously captured.…”
Section: Modeling Pseudocapacitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pilon et al proposed a one‐dimensional continuum model to simulate the time‐dependent charging behavior of a hybrid capacitor consisting of a pseudocapacitive metal oxide electrode for lithium‐ion intercalation and a carbon electrode for EDL formation ( Figure a) . Ion diffusion, lithium‐ion intercalation, and redox reaction were simultaneously captured.…”
Section: Modeling Pseudocapacitorsmentioning
confidence: 99%
“…In the case of a thin‐film electrode of fast Li‐intercalation, the CV curve suggests that the Faradaic process dominates in the whole voltage range (Figure b). In the case of a thick oxide electrode where the kinetics is limited by Li intercalation, they found that the Faradaic region is at more negative potential, while the capacitive region is at high potential and dominated by the EDL formation and that the transition between Faradaic and capacitive behavior occurred between these two regions …”
Section: Modeling Pseudocapacitorsmentioning
confidence: 99%
“…Other physicochemical phenomena may also contribute to the irreversible and/or reversible heat generation rates. For example, in hybrid supercapacitors, redox reactions also contribute to the reversible heat generation upon charging/discharging . In addition, the overpotential at the redox active electrode necessary to drive the redox reactions is responsible for irreversible “polarization heating” .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in hybrid supercapacitors, redox reactions also contribute to the reversible heat generation upon charging/discharging . In addition, the overpotential at the redox active electrode necessary to drive the redox reactions is responsible for irreversible “polarization heating” . Other possible sources of heat generation may be associated with ion solvation/desolvation and decomposition of the electrolyte at high potentials …”
Section: Introductionmentioning
confidence: 99%
“…The total heat Q generated in Hybrid SC can also be deduced from one-dimensional Stern electrochemical model [69], which describes the heat generation process, and expressed as:…”
Section: B Heat Generation Mechanism Of Hybrid Scmentioning
confidence: 99%